Evolving Bioprosthetic Tissue Calcification Can Be Quantified Using Serial Multislice CT Scanning - B. Meuris; H. De Praetere; W. Coudyzer; W. Flameng (International Journal of Biomaterials)
Background. We investigated the value of serial multislice CT scanning for in vivo determination of evolving tissue calcification in three separate experimental settings. Materials and Methods. Bioprosthetic valve tissue was implanted in three different conditions: (1) glutaraldehyde-fixed porcine stentless conduits in pulmonary position (); (2) glutaraldehyde-fixed stented pericardial valves in mitral position (); and (3) glutaraldehyde-fixed pericardial tissue as patch in the jugular vein and carotid artery (). Multislice CT scanning was performed at various time intervals. Results. In stentless conduits, the distribution of wall calcification can be reliably quantified with CT. After 20 weeks, the CT-determined mean calcium volume was 1831 ± 581 mm³, with a mean wall calcium content of 89.8 ± 44.4 μg/mg (). In stented pericardial valves implanted in mitral position, reliable determination of tissue mineralization is disturbed by scattering caused by the (continuously moving) alloy of the stent material. Pericardial patches in the neck vessels revealed progressive mineralization, with a significant increase in mean HU and calcium volume at 8 weeks after implantation, rising up to a level of 131.1 ± 39.6 mm³ (mean calcium volume score) and a mean calcium content of 19.1 ± 12.3 μg/mg. Conclusion. The process of bioprosthetic tissue mineralization can be visualized and quantified in vivo using multislice CT scanning. This allows determination of the kinetics of tissue mineralization with intermediate in vivo evaluations.